Surface Subsidence Velocity of Fully-Mechanized Thick Seam Top Coal Caving Mining - Wenbing Guo (International Conference on Ground Control in Mining, 2011)
Surface subsidence for fully mechanized thick seam top coal caving was measured, and surface subsidence characteristics were then analyzed. The subsidence initiation distance from the set-up room and the advance influence distance ahead of the advancing longwall face were studied. The maximum surface subsidence velocity and the delay angle of the maximum subsidence velocity were determined. The results indicated that surface movement was intensive, the surface subsidence velocity was very high, the ground surface was badly damaged, and the subsidence initiation distance from the set-up room was smaller than that in general geological and mining condition.